SPK DENGAN METODE SAW PEMBERIAN BANTUAN KELUARGA SEJAHTERA DI MASA PANDEMI COVID-19 - Enggi Elina Sari (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Purwodadi City in Menduran Village is one of the areas targeted by the government during the corona virus pandemic or the Covid-19 pandemic. The aid program is assistance from the government to serve the underprivileged. During the COVID19 pandemic, family welfare programs are expected to be able to obtain health, education, productivity, and family welfare rights. As long as village officials often feel uncomfortable because there is no information system to determine potential beneficiaries. In this context, the author uses a decision support system approach using the Simple Additive Weighting (SAW) method. This system can support beneficiary decision making during the COVID-19 pandemic based on certain criteria. DSS are designed to assist decision-making by starting with selecting data, relevant issues, deciding on the decision-making process, and deciding on alternative options